Students’ opinion about the implementation of European Higher Education Area in Physical Activity and Sport Sciences studies - Coterón López, Javier; Franco Álvarez, Evelia; Gil Ares, Javier (Revista Complutense de Educación, 2012)
The paper presents a descriptive analysis of the students’ opinion about the current university reality in the process of change promoted by Bologna Plan. The study was carried out in the Faculty of Physical Activity and Sport - INEF of the Technical University of Madrid. A validated questionnaire was administered to a sample composed by 282 students immersed in the Bologna Plan, and 203 students immersed in the one before. Results show differences according to the curriculum followed. In general terms students belonging to Bologna Plan showed more positive scores than students belonging to the plan before in regard of all analyzed aspects.